Navigating The Post Pandemic Crisis: Embracing Islamic Business Culture for Sustainability Through the Lens of Islamic Scholars - Sharifah Rahama Amirul; Sharija Che Shaari; Sharifah Milda Amirul (Fakulti Pengajian Islam, Universiti Malaysia Sabah, 2023)
Amidst the dynamic shifts in the global landscape, notably in the aftermath of the pandemic crisis of Covid-19, organisational culture (OC) has emerged as a research topic of interest because the unprecedented challenges of pandemic crisis significantly affect the culture and operations of organizations. Much of generalisability business research has converged on conventional business OC to limit the impact of COVID-19. Little attention has been given to the view of Islamic business in dealing with the pandemic crisis. This research paper delves into the implications of the post-pandemic world through the lens of Islamic scholars. It seeks to explore the role and significance of organizational culture in fostering sustainability and resilience, particularly within Islamic business contexts. Drawing inspiration from the deep well of Islamic wisdom, this paper offers insights and guidance on how organizations, guided by Islamic principles, can embrace and adapt their cultures to meet the demands of the evolving global landscape. Through the lens of Islamic scholars, a conceptual framework of Islamic business survival amidst pandemic crisis is proposed by embracing the true Islamic organisational culture for sustainability. The proposed framework should not be limited to crisis situations, but rather serve as a valuable resource for Islamic business sustainability.